2012
DOI: 10.16956/kjes.2012.12.4.231
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Malignancy in Thyroid Nodules Diagnosed as Follicular Neoplasm or Hürthle Cell Neoplasm on FNA

Abstract: Purpose:The rate of malignancy in the follicular neoplasm (FN) or Hürthle cell neoplasm (HCN) of the thyroid gland is estimated as approximately 20∼30%. Fine-needle aspiration biopsy (FNAB) and frozen section examination are restricted in differentiating between benign and malignant. The aims of this study are to compare the differences of clinicopathologic features and to determine the risk factors for malignancy in patients with FN or HCN. Methods: A retrospective study was conducted of patients with FN or H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Furthermore, old age, male sex, solitary nodule, and larger size of the nodule are thought to be associated with increased risk of malignancy [9,23] . In contrast, others reported that old age, male sex, larger nodule size, and solitary nodule are not predictive of malignancy [4,24] . Large nodule size has been defined variably among different researchers including > 3cm [9] , > 4cm [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, old age, male sex, solitary nodule, and larger size of the nodule are thought to be associated with increased risk of malignancy [9,23] . In contrast, others reported that old age, male sex, larger nodule size, and solitary nodule are not predictive of malignancy [4,24] . Large nodule size has been defined variably among different researchers including > 3cm [9] , > 4cm [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we couldn't analyze these parameters as predictors of malignancy. Though its reliability is questionable, the frozen section is sometimes used to identify malignancy intraoperatively and hence define the extent of surgery [7,24] . We attempted to evaluate intraoperative clinical evidence of malignancy as frozen section evaluation is not available in our setup.…”
Section: Discussionmentioning
confidence: 99%